ANALISA GEL KOMBINASI PLATELET RICH PLASMA DAN CHITOSAN TERHADAP PENINGKATAN JUMLAH OSTEOBLAS SEBAGAI BONE REGENERATION PADA LUKA PASCA EKSTRAKSI GIGI TIKUS WISTAR - Intan Maryani; Yayun Siti Rochmah; Anang Dwi Parmana (Odonto : Dental Journal, 2018)
Background: Extraction has been known as a method for removing the tooth from its socket. Although extraction is frequent, the incidence of post extraction complication are commonly found, about 2,6-30,9%. Complications can inhibit wound healing and bone regeneration of socket. PRP is Platelet Rich Plasma containing growth factors that plays an important role in wound healing, induces bone regeneration and stimulates osteoprogenitor cell into osteoblast cell. Chitosan is a chitin derivate that extracted from the crab shells through deacetylation stage. Chitosan properties are osteoinductive, biocompatible, biodegradable, cell proliferation, antimicrobial, antioxidant, antitumor, and stimulates growth factors capabilities. Purpose: To analyze the combination of PRP and Chitosan gel to increase the number of osteoblast in post extraction wound of wistar rat teeth.Method: True experimental post-test only control group design was done in 28 wistar rats. Sample were divided into 4 groups: PRP gel, combination PRP and Chitosan gel, Chitosan gel and control group Povidone Iodine. Dextra Mandible incisors were extracted and treated accordingly. Number of osteoblast in post extraction socket was observed microscopically after 14 days using IHC staining. Data analyzed by using One Way ANOVA parametric test followed by Post Hoc LSD test.Results: There were statically signifcant diﬀerence between number of osteoblast in combination PRP and Chitosan gel group compare to PRP gel group (p=0,736), Chitosan gel group (p=0,402) and Povidone Iodine group (p=0,613).Conclusion: Combination PRP and Chitosan gel has a good eﬀect in increasingnumber of osteoblast in wound healing post dental extraction